On the Use and Interpretation of Areola/Nipple Retention as a Biomarker for Anti-androgenic Effects in Rat Toxicity Studies - Schwartz, Camilla Lindgren; Christiansen, Sofie; Hass, Ulla; Ramhøj, Louise; Axelstad, Marta; Löbl, Nathalie Michelle; Svingen, Terje (Frontiers in Toxicology, 2021)
Areola/nipple retention (NR) is an established biomarker for an anti-androgenic mode of action in rat toxicity studies. It is a mandatory measurement under several OECD test guidelines and is typically assessed in combination with anogenital distance (AGD). Both NR and AGD are considered retrospective biomarkers of insufficient androgen signaling during the masculinization programming window in male fetuses. However, there are still aspects concerning NR as a biomarker for endocrine disruption that remains to be clarified. For instance, can NR be regarded a permanent adverse effect? Is it a redundant measurement if AGD is assessed in the same study? Is NR equally sensitive and specific to anti-androgenic chemical substances as a shortening of male AGD? In this review we discuss these and other aspects concerning the use of NR as a biomarker in toxicity studies. We have collected available literature from rat toxicity studies that have reported on NR and synthesized the data in order to draw a clearer picture about the sensitivity and specificity of NR as an effect biomarker for an anti-androgenic mode of action, including comparisons to AGD measurements. We carefully conclude that NR and AGD in rats for the most part display similar sensitivity and specificity, but that there are clear exceptions which support the continued assessment of both endpoints in relevant reproductive toxicity studies. Available literature also support the view that NR in infant male rats signifies a high risk for permanent nipples in adulthood. Finally, the literature suggests that the mechanisms of action leading from a chemical stressor event to either NR or short AGD in male offspring are overlapping with respect to canonical androgen signaling, yet differ with respect to other mechanisms of action.